Autocuidado en familiares cuidadores informales de pacientes con Alzheimer en Latinoamérica: revisión documental (2021)
The present documentary review investigation seeks to answer the following research question: What is the support provided from the health field to family caregivers of patients with Alzheimer's in Colombia? next general objective To describe the self-care practices carried out by informal family caregivers of Alzheimer's patients and what support is provided to them from the health systems in Latin America, by means of a documentary review. In the understanding that this disease in Colombia according to the figures of the Ministry of Health is increasing. This descriptive or informative and qualitative documentary research focuses on clinical and health psychology. The search engines used were Scielo, Redalyc, Dialnet, prioritizing research of high scientific diffusion, the categories used for the search were Alzheimer and Family, where 52 articles were consulted, of which 35 are used for the present research and the rest were discarded for not meeting the inclusion requirements, the results allowed establishing that there is a strong tendency to assume this issue from clinical psychology understanding this as a problem not only of mental health but also as something psychosocial and that this is the trend at the level of studies .